ANALISIS KINERJA KEUANGAN MENGGUNAKAN RASIO KEUANGAN PADA PT GOWA MAKASSAR TOURISM DEVELOPMENT TBK - Dirwan Dirwan; Gusmi Haerani (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
The formulation of the probelem is research is how performance PT Gowa Makassar Tourism Development Tbk measured based on the analysis of financial flows using financial statements using financial ratio analysis method. The method of analysis used is financial ratios which include: liquidity, solvency, profitability and activity. The results show the performance of PT Gowa Makassar Tourism Development Tbk which was on the liquidity ratio in 2014 to 2016 was in good condition, where the Current Ratio (CR) of the company in 2014 to 2016 was more than 100% which means PT GMTD Tbk able to pay all obligation smoothly with current assets available. Overall quick ratio (QR) had a poor performance due to the increase in the value of current debt. The condition Solvency ratio of PT Gowa Makassar Tourism Development Tbk was good enorghin 2014 until 2016, which Debt To Assets Ratio (DAR) company in 2014 until 2016 more then 100%. This percentage indicates that the financial condition was quite good because their debt as financing for large assets compared with own capital. Performance in debt to equity ratio (DER) Companies was not good because DER greater than 90% indicates that the sources of the companis assets financing comes more from debt than its own capital. Profitability ratio of PT Gowa Makassar Tourism Development Tbk in 2014 until 2016 was good, where the result of the profitabily ratio is higher then one year time deposit interest rates. The activity ratio of PT Gowa Makassar Tourism Development Tbk in 2014 to 2016 was good, where Total Assets Turn Over (TATO) is more then 1 (one), that means the company, was productive in generating sales.